Dementia among Elderly Melanau: A Community Survey of an Indigenous People in East Malaysia - Pu'un, Bawih Inu; Othman, Zahiruddin; Drahman, Ismail (Japan International Cultural Exchange Foundation, 2014)
Background: Prevalence of cognitive impairment and dementia among indigenous population were noted by previous studies to be exceptionally high at 66.7% and 32.2, respectively. Objectives: This study aimed to determine the prevalence of dementia and identify the associated risk factors among elderly Melanau, an indigenous population in Sarawak. Methods: All eligible and available elderly Melanau in 8 out of 32 villages in Mukah district were screened with ECAQ. Clinical interview by trained researcher was conducted on subjects with score 5 and below to ascertain the dementia diagnosis. Results: A total of 344 subjects, which constituted about 28% of the elderly Melanau population (mean age 70.4 ± 6.7) were screened. The prevalence of cognitive impairment and dementia among elderly Melanau was 27.3% and 10.5%, respectively. Dementia was independently associated with age (OR 1.19), no education (OR 7.56) and multiple CVS illnesses (OR 3.76). Conclusion: The prevalence of dementia among elderly Melanau is higher compared to in Malays. It is important to promote mental health and healthy lifestyle. Particular attention should be given to vascular risk factors to reduced risk of dementia